Diabetes and Covid: Severity is inevitable??? - Rao, Bhagya Venkanna (Journal of Pharmacy Practice and Community Medicine)
Dear Readers,In the last 30 years, diabetes has become more frequent, with more than 400 million individuals worldwide living with the disease. Unfortunately, around half of them are unaware that they have diabetes. They have not been diagnosed, and those who have been diagnosed lack access to the medicines and health services they require. COVID-19 and diabetes mellitus have a complex and bidirectional connection. Read More ….